The Influence of Exclusive Breastfeeding to Emotional Development of Children Aged 48-60 Months - Kusmiyati, Yuni; Sumarah, Sumarah; Dwiawati, Nurul; Widyasih, Hesty; Widyastuti, Yani; Haji Abdul Mumin, Khadizah (UI Scholars Hub, 2018)
Impaired emotional development is a problem faced by children and this can negatively impact on function, development and readiness of their school. Exclusive breastfeeding is able to meet brain development needs that affect child development. This study aimed to determine correlation between exclusive breastfeeding and emotional development of children aged 48-60 months. This study used historical cohort.The subjects of this study were 7-12-month old infants living in area of Borobudur Primary Health Care Primary Health Care, Central Java Province, Indonesia in 2011-2012. Independent variable of exclusive breastfeeding was when infants received only breast milk without any supplementary food or drink including water since birth until the age of 6 months. Data were obtained from medical records of children. The emotional development was assessed directly by using questionnaires on emotional and mental problems. Data analysis used cox regression. This study found that provision of exclusive breast milk was evidently correlated with child’s emotional development. Infants who did not receive exclusive breastfeeding had 2.96 higher risk of having abnormal emotional development than infants who received exclusive breastfeeding. Exclusive breastfeeding greatly influences emotional development of the child.